The role of KNDy neurons in human reproductive health - Aki Oride; Haruhiko Kanasaki (Endocrine Journal)
In the early 2000s, metastin, an endogenous ligand for G protein-coupled receptor 54 (GPR54), was discovered in human placental extracts. In 2003, GPR54 receptor mutations were found in a family with congenital hypogonadotropic hypogonadism. Metastin was subsequently renamed kisspeptin after its coding gene, Kiss1. Since then, studies in mice and other animals have revealed that kisspeptin is located at the apex of the hypothalamic-pituitary-gonadal axis and regulates reproductive functions by modulating gonadotropin-releasing hormone (GnRH). In rodents, kisspeptin (Kiss1) neurons localize to two regions, the hypothalamic arcuate nucleus (ARC) and the anteroventral periventricular nucleus (AVPV). ARC Kiss1 neurons co-express neurokinin B (NKB) and dynorphin and are thus termed KNDy neurons. Kiss1 neurons in humans are concentrated in the infundibular nucleus (equivalent to the ARC), with few Kiss1 neurons localized to the preoptic area (equivalent to the AVPV), and the mechanisms underlying GnRH surge secretion in humans are poorly understood. However, peripheral administration of kisspeptin to humans promotes gonadotropin secretion, and administration of kisspeptin to patients with hypothalamic amenorrhea or congenital hypogonadotropic hypogonadism restores the pulsatile secretion of GnRH/luteinizing hormone. Thus, kisspeptin undoubtedly plays an important role in reproductive function in humans. Studies are currently underway to develop kisspeptin receptor agonists or antagonists for clinical application. Modification of KNDy neurons by NKB agonists/antagonists is also being attempted to develop therapeutic agents for various menstrual abnormalities, including polycystic ovary syndrome and menopausal hot flashes. Here, we review the role of kisspeptin in humans and its clinical applications.